Design and Development of an Automatic Wiping Board System - Nuță Andrei-Bogdan; Ulmeanu Mihaela-Elena; Doicin Cristian-Vasile (Communications of International Proceedings, 2020)
This research is mainly addressed to educational institutions of any level, whether it is a gymnasium, high school or a higher education institution, and it aims to modernize the current and future learning environment by offering an easily implementable solution for wiping board systems. The current research paper proposes a project which focuses on improving the quality of the classes and presentations through offering additional value and designing a more convenient learning environment for both students and teachers. The proposed concept product has been designed to be reproduced in any circumstance by a person or a team that has background knowledge in mechanics, mechatronics, additive technologies and electronics. This system was built based on the analysis of several criteria such as: ease of maintenance, appearance attractiveness, functionality of the writing/ wiping surface. Three main requirements of the wiping surface were to facilitate the board to be watered and to ease the movements along it, and to allow remote control. The criteria were included in a questionnaire which targeted at relevant respondents in order to collect data, to receive feedback and to analyse the competitive products. The products’ components were selected from the market in order to have the most diversified functions and to meet various needs such as internet connection or the possibility of moving or changing the writing instrument. Based on these functions, multiple sets of tables have been prepared to analyse the factors that have the greatest impact; two relevant analyses are represented by Quality function deployment and conceptual analysis. These analyses ensured the development of an optimal product concept which can be effectively used both as a stand-alone product and as a learning environment for students as it represents an example of mechatronics, electronics and additive technologies.
Keywords: Automatic Wiping Board; Conceptual Design; Learning Objectives; Learning Environment.